Molecular identification of fungi isolated from bean tissues with anthracnose symptoms (2014)
ABSTRACTIn this work, endophytic fungi from leaves and pods of bean presenting anthracnose symptoms were isolated from plantscollected at different municipalities in the province of Antioquia (Colombia). Isolates were identified by sequencing the rDNA ITS regions together with the examination of reproductive structures during sporulation in culture media. Colletotrichum lindemuthianum, the causal agent of anthracnose was isolated in all samples showing symptoms of this disease. These results were confirmed by duplex PCR using the specific primers CD1/CD2 and CY1/CY2. Additionally, 17 endophytic fungi were obtained. Fourteen isolates did not sporulate in culture media (Mycelia sterilia) but were identified by phylogenetic analysis of the ITS regions as the Ascomycetes: Leptosphaerulina (3), Diaporthe (3), Gibberella (1), Plectosphaerella (1) and Biscogniauxia (1)and the mitosporic genera Phoma (2), Alternaria (2) and Stemphylium(1). Three isolates were identified combining morphologica and molecular analysis as Fusarium (2) and Curvularia lunata (1). This work increases our knowledge of the mycobiota of legume plants and will serve as support of future studies aimed at determining the effect of these fungi on the development of anthracnose as well as other problems affecting the bean crop.IDENTIFICACIÓN MOLECULAR DE HONGOS AISLADOS DETEJIDOS DE FRÍJOL CON SÍNTOMAS DE ANTRACNOSISRESUMENEn este estudio se realizó el aislamiento de hongos en tejidos foliares y vainas de fríjol con síntomas de antracnosis, procedentes de cultivos de diferentes municipios del departamento de Antioquia (Colombia). La identificación de los aislamientos se realizó con base en la secuenciación de las regiones ITS del ADN ribosomal y se confirmó por observación microscópica de estructuras reproductivas en aquellos aislamientos que esporulaban en medios de cultivo. En todas las muestras sintomáticas, se logró el aislamiento del agente causal de la antracnosis, Colletotrichum lindemuthianum, siendo confirmada su identidad porPCR dúplex con cebadores específicos CD1/CD2 y CY1/CY2. En adición se obtuvieron 17 hongos endófitos, 14 de los cuales no esporularon en medio de cultivo (Mycelia sterilia), siendo identificados mediante análisis filogenéticos de regiones ITS como miembros de los Ascomycetes Leptosphaerulina (tres aislamientos), Diaporthe (tres aislamientos), Gibberella (un aislamiento),Plectosphaerella (un aislamiento) y Biscogniauxia (un aislamiento); y de los géneros mitospóricos: Phoma (dos aislamientos), Alternaria (dos aislamientos) y Stemphylium (un aislamiento). Los tres hongos restantes se identificaron con base en caracteres morfológicos y secuenciación como miembros de los géneros Fusarium (dos aislamientos) y de la especie Curvularia lunata (un aislamiento). Este estudio aumenta el conocimiento de la micobiota de leguminosas, como base para el desarrollo de estudios futuros que permitan evaluar el efecto de estos hongos sobre el desarrollo de enfermedades como la antracnosis y de otrosproblemas bióticos y abióticos del cultivo del fríjol.